Infiltrative Therapy of Morton’s Neuroma: A Systematic Review of Different Treatment Options - Lorenzon, Paolo; Rettore, Carlo; Scalvi, Andrea (Acta Biomedica Atenei Parmensis, 2022)
The aim of this study is to systematically review the literature on clinical outcomes of patients who have undergone infiltrative therapy for treatment of Morton’s neuroma. As many kinds of substances are injected, the main outcome defines which treatment provides the best results in term of patient’s satisfaction and pain relief, so that it would be possible to choose the best option.Many electronic databases were searched on July 2021; we have included prospective and retrospective case series, and randomized controlled trials of infiltrative treatments in patients with primary diagnosis of Morton’s neuroma.The search returned 25 studies which met the inclusion criteria, with a total of 2243 cases. The incidence of outcomes was extracted and analyzed.Although many studies demonstrated favorable results in terms of pain relief and patient’s satisfaction employing different substances for infiltration, alcohol injection appears results on long run.